Soil fertility attributes and the occurrence of nematodes in soybean crop (Research, Society and Development, 2023)
The soybean crop is increasing due to the presence of phytomatoides. Based on this, the objective of this research is to identify and analyze the occurrence of nematodes in soybean crop under the effect of soil physical and chemical characteristics. The study was conducted in two areas with soybean plantation at Olhos D' Água Farm, Ceres-Goiás. After collection, the samples were taken to the laboratory, starting the physical, chemical and nematological analyzes of soil samples from the area. For the extraction process of nematodes, the methods of fluctuation-sedimentation and sieving were used followed by the technique of clarifying the samples. After the analysis and extraction processes, the samples were taken to the microscopy laboratory, starting the identification and quantification of nematodes. The data obtained were submitted to the Main Component Analysis (PCA) method, with the help of the Past software. The presence of four different genera of nematodes, Pratylenchus spp., Helicotylenchus spp., Meloidogyne spp. and Heterodera spp.